Clinical effectiveness of internet-based cognitive behavioral therapy for insomnia in routine secondary care: results of a randomized controlled trial - Pchelina, Polina; Poluektov, Mikhail; Krieger, Tobias; Duss, Simone B.; Berger, Thomas (Frontiers in Psychiatry, 2024)
Introduction: Delivering cognitive-behavioral therapy for insomnia over the internet bears the advantage of accessibility and uptake to many patients suffering from chronic insomnia. In the current study, we aimed to investigate the effectiveness of internet-based cognitive-behavioral therapy for insomnia (iCBT-I) in routine care.We conducted a two-arm non-blinded randomized controlled trial with care as usual (CAU) as a control condition. Participants were recruited in a specialized outpatient sleep medicine department. Both arms had access to other healthcare resources and the intervention group had access to the iCBT-I program for two months. The primary outcome was insomnia severity, measured by the Insomnia severity index (ISI). Secondary outcomes were fatigue severity, daytime sleepiness, affective symptoms, dysfunctional beliefs and attitudes about sleep, sleep locus of control, sleep hygiene, sleep efficiency (SE), sleep onset latency, wake after sleep onset (WASO), total sleep time (TST). Linear mixed models for repeated measures were used to analyze the longitudinal data at baseline, post-treatment, and after three months of follow-up. The trial was registered at www.clinicaltrials.gov (NCT04300218 21.04.2020).The results showed a significant time*group interaction effect (p=.001) at post-treatment with between-group effect size (d=0.51), indicating that the ISI decreased by 3.8 scores more in the iCBT-I group than in the CAU group. There was no significant difference in ISI between groups at follow- up. Regarding secondary outcomes, dysfunctional beliefs about sleep, SE, and WASO decreased significantly during treatment in the intervention group with between-group effect sizes d=0. 35, d=-0.51, and d=0.47, respectively. At the follow-up, between-group effects on DBAS and SE remained significant: d=0.36 and d=-0.63, respectively. For TST, we observed a significant time*group effect of d=-0.38 only after follow-up.Our findings suggest that iCBT-I has a significant effect on insomnia severity at posttreatment compared to CAU. iCBT-I further improved dysfunctional beliefs about sleep and improved subjective sleep characteristics, such as sleep efficiency, wake time after sleep onset and total sleep time during 3 months after treatment.